ANALISIS VIDEO TIKTOK EASY GERMAN ESSEN UND TRINKEN SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA JERMAN KELAS XI - Chikka Prameswari,; Ari pujosusanto, (LATERNE, 2025)
This study aimed to analyze the relevance of video content themed Essen und Trinken on the TikTok account Easy German to the needs of teaching German speaking skills for eleventh-grade students based on the Kurikulum Merdeka. The research method used descriptive qualitative with content analysis techniques applied to ten selected videos. The research instrument was a validation checklist based on six audiovisual media selection criteria according to Prastowo. The results showed that most videos scored above 70% in relevance, indicating that they were appropriate and highly appropriate as learning media. Easy German videos provided thematic vocabulary, simple sentence structures, and contextual dialogue models aligned with the learning outcomes of phase F in the Kurikulum Merdeka. Therefore, the Easy German TikTok account could be utilized as an effective, engaging, and contextual alternative medium for teaching German speaking skills.